2021
DOI: 10.1249/mss.0000000000002833
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Metabolic Costs of Heavy Military Backpacking

Abstract: IntroductionExisting predictive equations underestimate the metabolic costs of heavy military load carriage. Metabolic costs are specific to each type of military equipment, and backpack loads often impose the most sustained burden on the dismounted warfighter.PurposeThis study aimed to develop and validate an equation for estimating metabolic rates during heavy backpacking for the US Army Load Carriage Decision Aid (LCDA), an integrated software mission planning tool.MethodsThirty healthy, active military-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…When accounting for all the physiological parameters and ruck grade, predictive ruck metabolic equations revealed that the average participant in this study expended 270 kcal/h (Looney et al, 2022).…”
Section: Performance Was Comparable Between the Kb And Cbmentioning
confidence: 83%
“…When accounting for all the physiological parameters and ruck grade, predictive ruck metabolic equations revealed that the average participant in this study expended 270 kcal/h (Looney et al, 2022).…”
Section: Performance Was Comparable Between the Kb And Cbmentioning
confidence: 83%
“…Design. The design of the present study mirrored that of our previous article on military backpack loading (13) with few exceptions. Steady-state metabolic rate (M ˙) data were collected from healthy, active military-age men and women at walking speeds up to 1.97 m•s −1 while unloaded (0% body mass) and when carrying three vest-borne loads (22%, 44%, and 66% body mass).…”
Section: Methodsmentioning
confidence: 97%
“…Metabolic rate (M ˙) is divided into a resting component (M ˙Rest ) as well as two active components for standing (M ˙Stand ) and walking (M ˙Walk ) multiplied by a load factor (load). The M ˙Walk component includes a terrain coefficient for different walking surfaces (9,10), two level walking terms (11,13), and a graded walking term (12). The load factor consists of individual terms for different types of carried equipment, including backpack (13) and vest-borne loads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…US Army doctrine on work/rest guidance is based on the inclusion of Ṁ estimates into sophisticated thermophysiological models that forecast core body temperature changes for a typical warfighter depending on the environmental conditions (63,78). Although recent studies focused on deriving optimized walking equations for modern military personnel (53)(54)(55)69,70), there has yet to be a concerted effort to develop a similar series of equations for running.…”
Section: Introductionmentioning
confidence: 99%